Les Temps Chauds. - Bélisle, Josée; Gascon, France; Godmer, Gilles; Landry, Pierre; Lussier, Réal (Montréal : Musée d'Art Contemporain, 1988)
April, Raymonde ; Blain, Dominique ; Bouchard, Sylvie ; Corriveau, Thomas ; Derome, Nathalie ; Dutkeuych, Andrew ; Gauthier, Christiane ; Goodwin, Betty ; Goulet, Michel ; Granche, Pierre ; Hunter, Paul ; Laliberté, Sylvie ; Lavoie, Raymond ; Mihalcean, Gilles ; Moore, David ; Murphy, Serge ; Poulin, Roland ; Safdie, Sylvia ; Saulnier, Michel ; Sauré, Danielle ; Tousignant, Serge ; Townsend, Martha ; Wainio, Carol ; Waquant, Michèle
Les Temps Chauds, Musée d'Art Contemporain de Montréal, 1er juin - 11 septembre 1988
boek